Identifying How Customer’s Loyalty and Retention Influences Relationship Marketing in A Hotel Industry - Pathmananathan, P. Ravindran; Aseh, Khairi (Archives of Business Research, 2021)
In today’s diverse global market place, relationship marketing has been recognised as an excellent way to develop an exclusive long-term relationship with their clients. Many organizations, on the other hand, struggle to systematically measure and monitor customer retention and the factors that influence it. Personal connection and service quality are becoming increasingly important to a growing number of businesses. The aim of this research is to emphasize the significance of personal connection and service quality in the service industry. This research was conducted using a questionnaire that was distributed to 200 hotel guests in urban areas such as Georgetown and Penang. It can be concluded that customer loyalty and customer retention play an important role in relationship marketing. As a result, the higher the degree of personal connection and service quality, the more likely it is that a customer will return to the hotel and recommend it to others.